Factors related to teacher turnover in special education - Paqueo, Elisa B. (1979)
This study compared stayers and leavers in terms of personal attributes and job satisfaction in order to draw a stayer typology and leaver typology using two groups of subjects randomly selected from the population of SPED teachers in Regions 4 and 7. There was no significant difference between the stayers and the leavers in their reasons for joining the SPED training program. Very minimal difference exists in terms of their personal attributes and job satisfaction/dissatisfaction. The subjects estimated the cost or burden involved in teaching SPED classes to be average although the leavers among regular teachers found the tasks or workload more burdensome than the stayers. Age prior to training in SPED is negatively related to turnover.
Mimeographed.
Thesis (D.Ed.)--University of the Philippines, Diliman.
Keywords: Teacher turnover -- Philippines -- Manila metropolitan area; Exceptional children -- Education -- Philippines; Teacher turnover -- Philippines -- Central Visayas; Teacher turnover -- Philippines -- Southern Tagalog